2020
DOI: 10.1016/j.chemphyslip.2020.104895
|View full text |Cite
|
Sign up to set email alerts
|

An elegant technology for ultrasensitive impedimetric and voltammetric determination of cholestanol based on a novel molecularly imprinted electrochemical sensor

Abstract: In this work, a novel molecularly imprinted electrochemical sensor (MIES) has been fabricated based on electropolymerization of a molecularly imprinted polymer (MIP) onto a glassy carbon electrode (GCE) modified with gold-palladium alloy nanoparticles (AuPd NPs)/polydopamine film (PDA)/multiwalled carbon nanotubeschitosan-ionic liquid (MWCNTs-CS-IL) for voltammetric and impedimetric determination of cholestanol (CHO).Modifications applied to the bare GCE formed an excellent biocompatible composite film which w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…To increase conductivity and obtain a better signal, graphite powder [33] and nanoparticles [71][72][73] have been included in these sensors. Morphine [21,56], ephedrine [57], paracetamol [58], dopamine [59,71], homovanillic acid [74], atrazine [60], creatinine [61], cholestanol [64], triacetone triperoxide [24], 2,4,6-trinitrotoluene, and 1,3,5-trinitroperhydro-1,3,5-triazine explosives [63] (see Table 1 for the characteristics of these sensors) are representative analytes. The analytic results obtained for the detection of creatinine using a MIP-based sensor showed comparable precision and accuracy with results obtained by HPLC [61].…”
Section: Voltametric and Amperometric Sensorsmentioning
confidence: 99%
“…To increase conductivity and obtain a better signal, graphite powder [33] and nanoparticles [71][72][73] have been included in these sensors. Morphine [21,56], ephedrine [57], paracetamol [58], dopamine [59,71], homovanillic acid [74], atrazine [60], creatinine [61], cholestanol [64], triacetone triperoxide [24], 2,4,6-trinitrotoluene, and 1,3,5-trinitroperhydro-1,3,5-triazine explosives [63] (see Table 1 for the characteristics of these sensors) are representative analytes. The analytic results obtained for the detection of creatinine using a MIP-based sensor showed comparable precision and accuracy with results obtained by HPLC [61].…”
Section: Voltametric and Amperometric Sensorsmentioning
confidence: 99%
“…Consequently, they observed that the effective imprinting site could be greatly affecting the sensitivity of the sensor. Moreover, the specificity of the sensor is poor, as the concentration of 1.0 µM vitamin D3, 0.1 µM progesterone, and 10.0 µM cholesterol can significantly affect the result [ 141 ]. In another study, Boobphahom et al detected the creatinine in serum sample on a non-enzymatic, electrochemical technique integrated paper-based microfluidic device.…”
Section: Ionic Liquids–carbon-based Functional Nanomaterials In Biosensing Applicationsmentioning
confidence: 99%
“…The medium was added dropwise to the vial and then its contents were taken out and centrifuged with the medium in 15 cc sterile test tubes. After centrifugation, the supernatant was removed and the cells were suspended again in the medium and transferred to a pre-prepared flask containing the medium and FBS and incubated (Hemmati et al, 2020;Jalalvand et al, 2020;Liu et al, 2020;Mahdavi et al, 2019;Nematpour et al, 2020;Zangeneh et al, 2019).…”
Section: Anti-human Oral Squamous Cell Carcinoma Studiesmentioning
confidence: 99%
“…In another column, it was considered to contain culture medium and healthy cells and in other columns, it was considered to contain culture medium and cell line cells. One of these columns, which contained culture medium and cells and did not contain Nevadensin, was considered as a control (Hemmati et al, 2020;Jalalvand et al, 2020;Liu et al, 2020;Mahdavi et al, 2019;Nematpour et al, 2020;Zangeneh et al, 2019).…”
Section: Anti-human Oral Squamous Cell Carcinoma Studiesmentioning
confidence: 99%
See 1 more Smart Citation